Penerapan Gaya Kepemimpinan Egaliter Orang Minahasa di Universitas Negeri Manado - Santie, Yoseph Daniel Ari; Mamonto, Fitri Herawati; Lasut, Meiske; Mesra, Romi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research wants to see what the egalitarian leadership style of the Minahasa people is like that is applied at Manado State University, where basically the leaders at UNIMA come from the Minahasa people as an indigenous tribe where UNIMA is located. The research method used is a qualitative research method with observation and interview data collection methods. While the data analysis used from Miles Huberman is in the form of data collection, data reduction, data presentation and drawing conclusions. The results of this study explain that leaders are easy to contact and meet, support from the social work environment is very important for leader effectiveness, leader effectiveness must go down directly to the bottom, and leaders provide rewards and punishments directly